2018
DOI: 10.1016/j.enbuild.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis of a cross-flow membrane-based parallel-plate liquid desiccant dehumidification system: Numerical and experimental data

Abstract: Operating parameters of a membrane-based parallel-plate liquid desiccant dehumidification system are investigated in this paper. The liquid desiccant and air are in a cross-flow arrangement, and separated by semi-permeable membranes to avoid carry-over problem. A numerical model is developed to simulate the system performance, and validated by experimental and analytical results. Impacts of main operating parameters on the system performance (i.e. sensible, latent and total effectiveness) are evaluated, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Bai et al [14,15] experimentally and numerically studied the coupled heat and mass transfer of a full-scale flat-plate membrane-based dehumidifier, and found that and mass flow rate ratio ( * ) are the key parameters influencing the dehumidifier performance, and their effects are interacted with each other. Su et al [16] proposed a solarpowered absorption chiller combined with a liquid desiccant dehumidifier for space cooling and fresh water production, and their results reveals that the exergy efficiency for the proposed system is 2.97% higher than the reference system. Huang et al [17,18] studied the conjugate heat and mass transfer in a membrane parallel-plate contractor, and analysed the effects of local and mean friction factors, Nusselt number and Sherwood number.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Bai et al [14,15] experimentally and numerically studied the coupled heat and mass transfer of a full-scale flat-plate membrane-based dehumidifier, and found that and mass flow rate ratio ( * ) are the key parameters influencing the dehumidifier performance, and their effects are interacted with each other. Su et al [16] proposed a solarpowered absorption chiller combined with a liquid desiccant dehumidifier for space cooling and fresh water production, and their results reveals that the exergy efficiency for the proposed system is 2.97% higher than the reference system. Huang et al [17,18] studied the conjugate heat and mass transfer in a membrane parallel-plate contractor, and analysed the effects of local and mean friction factors, Nusselt number and Sherwood number.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In the last years, new perspectives in the desiccant cooling system (DCS) have been derived, which are helpful to achieve an energy-efficient design by the heat-driven cooling equipment [ 11 ]. Thus, several studies analysed the impacts of the main operating parameters on systems performance [ 12 ], including dimensionless indicators, chemical solution properties and inlet air conditions, so as to improve the technologies deployment and their readiness [ 13 , 14 ]. Recently, Alahmer and Ajib reported in their impressive literature review which are the main barriers, challenges, and perspectives of solar cooling technologies wide deployment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moghaddam et al [23] introduced a solution-side effectiveness to evaluate the impact of * on dehumidification and regeneration processes, and pointed out that the latent effectiveness difference between the air-side and the solution-side is can be neglected. Bai et al [24,25] experimentally and theoretically studied the operating characters of a parallel-plate membrane-based dehumidification system by focusing on various parameters, and identified the effects of and mass flow rate ratio ( * ) are interacted with each other. Some researchers developed different types of the membrane-based contractor.…”
Section: Introductionmentioning
confidence: 99%